MULTIKULTURALISME DALAM PERSPEKTIF ISLAM - Mustapa, Nasip (JURNAL PENELITIAN KEISLAMAN, 2014)
We have well informed that before term âmulticulturalismâ occurs to the front, Islam is a religion that succeeds in creating multicultural society in Medina, Baghdad, Palestine and Andalusia either in academic conceptual or in historical reality. Therefore, Islam social history is quite different with the one from western religious life which imposed theocratic system and devastating religion conflict for centuries. Eventually these made terrible religion and historical traumatic for western people. It made the renaissance age came into being which ended with secularism â liberalism and the separation of religious values from daily life come into being. This understanding then has embedded into Muslim thought and become challenges for activists who want to spread multicultural values in multicultural Indonesia. Such efforts require new concepts and frameworks in order to address the understanding that have been become an absolute thought in every Moeslemâs mind. Because if multiculturalism thought is forcefully imposed to the society, it will stoke negative reaction and reap unexpected outcome which are not suitable to the values of multiculturalism itself. Some efforts are necessary to do and one of which is revising the terms or redefining the terms of multiculturalism in order to avoid contra position against Islam. This conclusion obtained after doing a discussion with qualitative research with analytic descriptive method and library research.